Poliovirus Excretion in Children with Primary Immunodeficiency Disorders, India - Madhu Chhanda Mohanty; Manisha Rajan Madkaikar; Mukesh Desai; Prasad Taur; Uma Prajwal Nalavade; Deepa Kailash Sharma; Maya Gupta; Aparna Dalvi; Snehal Shabrish; Manasi Kulkarni; Jahnavi Aluri; Jagadish Mohanrao Deshpande (Emerging Infectious Diseases, 2017)
Prolonged excretion of poliovirus can occur in immunodeficient patients who receive oral polio vaccine, which may lead to propagation of highly divergent vaccine-derived polioviruses (VDPVs), posing a concern for global polio eradication. This study aimed to estimate the proportion of primary immunodeficient children with enterovirus infection and to identify the long-term polio/nonpolio enterovirus excreters in a tertiary care unit in Mumbai, India. During September 2014–April 2017, 151 patients received diagnoses of primary immunodeficiency (PID). We isolated 8 enteroviruses (3 polioviruses and 5 nonpolio enteroviruses) in cell culture of 105 fecal samples collected from 42 patients. Only 1 patient with severe combined immunodeficiency was identified as a long-term VDPV3 excreter (for 2 years after identification of infection). Our results show that the risk of enterovirus excretion among children in India with PID is low; however, systematic screening is necessary to identify long-term poliovirus excreters until the use of oral polio vaccine is stopped.